ETHICS, ART, AND SOCIAL WORK: A Necessary Conversation - Wehbi, Samantha (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2017)
There has been a growing interest in bringing creative arts as methods and processes into social work education and practice to enhance student learning and contribute to practices tackling issues of social justice and anti-oppression. This paper builds on the current conversation about the intersection of art and social work to propose the need for engagement with ethical considerations to guide our practice. Relying on examples of arts-informed and arts-based projects that tackle issues of ableism and racism, the discussion focuses on the need to consider issues of consent, representation, appropriation and agency of participants in these projects. Borrowing from the metaphor of photographic practice, the article concludes by proposing three ethical principles to guide arts-informed and arts-based practices in social work.